RESEARCH ON RECEIVING GRAIN FROM ROAD TRANSPORT - SOKOLOVSKA, OLENA; VALEVSKA, LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
At grain elevators and grain receiving enterprises, the operation of receiving grain from vehicles is the main one. Many elevators of other types also accept grain from vehicles due to the fact that this allows improving the economic performance of the enterprise, and in general, the combination of functions inherent in elevators of different types is a feature of enterprises in the grain elevator industry of our country. For almost all elevators or grain terminals, the issue of vehicle queues before entry is acute. The main means of mechanizing the unloading of grain crops from vehicles at enterprises in the grain elevator industry are truck unloaders. The introduction of various high-performance truck unloaders contributes to increasing the throughput capacity of elevators for unloading grain from vehicles and road trains of all types. The process of receiving grain from vehicles consists of several operations, and each operation in this chain is important in reducing the time the vehicle spends at the enterprise, and therefore increasing its throughput. We analyzed the process of unloading vehicles on modern vehicle unloaders installed on various grain elevators. During the implementation of this study, we timed the process of unloading 20 single vehicles (i.e., without trailers) that delivered grain to the enterprise. The main stages of unloading vehicles in the receiving devices of the studied enterprises were identified and the average (most reliable), minimum and maximum execution time of each stage was determined. Timetables of unloading vehicles with wheat grain at the elevators where the research was conducted were constructed. The results of the timed unloading of vehicles in the receiving device showed that the longest stage is the stage of lifting the vehicle weigher platform and pouring grain, and the shortest stage is the driver’s exit from the cabin. The average duration of unloading vehicles was determined. It should be noted that the time of raising and lowering the platforms of truck unloaders at the enterprises under consideration corresponds to the passport data, that is, the truck unloaders do not operate with maximum efficiency. The enterprises where the research was conducted have a reserve for increasing the acceptance of grain from vehicles.